Development of a Physics Module Using Jampea Island Fishermen's Local Wisdom - Qaddafi, Muhammad; Roni Ririn; Anas Irwan; Muhammad Rusmin (Jurnal Pendidikan Fisika, 2026)
Physics education in schools often remains theoretical and disconnected from students' daily experiences, leading to decreased interest and limited conceptual understanding. One way to address this issue is by incorporating local knowledge into teaching materials to make learning more relevant and applicable to real life. This study aims to develop and evaluate the viability of a physics learning module based on the indigenous knowledge of fishermen on Jampea Island, Indonesia, specifically about sea tides, for senior high school students. The research used a development approach with the ADDIE model, which includes analysis, design, development, implementation, and evaluation phases. The module was validated by two experts, and a small trial was conducted with 24 Grade X Science students at SMA Negeri 4 Selayar Islands Regency. Data was collected through validation sheets, student response questionnaires, and learning outcome tests, then analyzed using Aiken’s V and descriptive percentage analysis. Results show that the module achieved very high validity, with an average Aiken’s V of 0.84. In terms of practicality, 54.7% of students rated the module as very practical, while 45.3% found it practical; all teachers (100%) evaluated it as very practical. Effectiveness analysis indicated that 75% of students attained learning mastery above the Minimum Completeness Criteria, demonstrating the module's success in improving learning outcomes. The novelty of this research lies in the systematic integration of Jampea Island fishermen’s local wisdom into physics education through the ADDIE model, supported by empirical validation of its validity, practicality, and effectiveness. In conclusion, this locally based physics module is both feasible and effective for classroom use. It enriches physics education by providing a culturally responsive and contextual learning model that enhances students’ conceptual understanding and engagement.